Tantaloniobatos com estrutura de perovskitas lamelares KCa2Nb(3-x)TaxO10 e seus derivados para aplicações em fotocatálise - Carreiro, Arnayra Sonayra de Brito Silva (2019)
Lamellar perovskites have been distinguished due to their properties, such as ionic conductivity, intercalation, photoluminescence, ion exchange and photocatalysis. Lamellar niobates and tantalates are composed by negatively charged lamellae and intercalated cations, especially a Dion-Jacobson phase, with formula M[An-1BnO3n+ 1]. In view of the related properties, this work aimed to synthesize and characterize the KCa2Nb(3-x)TaxO10 system, in order to determine the best synthesis conditions, the topochemical modifications for photocatalytic tests in the photohydroxylation with terephthalic acid and discoloration of an anionic dye in the case of Remazol Ouro Amarelo (RNL). X-ray diffraction (XRD), ultraviolet and visible (UV-Vis) absorption spectroscopy, infrared (IR) vibration spectroscopy, Raman spectroscopy, Scanning eletron microscopy (SEM), EDX analysis coupled to SEM and elemental nitrogen analysis and thermogravimetric analysis (TG / DTA). XRD indicated materials presented long range order. The IR and Raman confirm modifications made in pure oxides, as well as the differences present in the of nitriding, protonation and exfoliation. Elemental indicated the interconversion phase of the Dion Jacobson (DJ) to the Ruddlesden Popper (RP). The micrographs showed presence of plates, regardless of the undergone process. MET images confirm the presence of nanosheets after the exfoliation process. For the photohydroxylation reactions with terephthalic acid, the KCa2Nb2TaO10 system shows a better result. In the model dye (RNL) tests, KCa2Ta3O10 presented better photocatalytic efficiency. The photocatalytic mechanism for the KCa2Nb2TaO10 and KCa2Ta3O10 system is sensitive to both hole (h+) and electron (e−) and the formation of the hydroxyl radicals have a contribution of these two photogenerated charge carriers. In contrast, no significant results were observed for oxynitrides.